The Future of Sub-National Governments in a Supra-National World - Lessons from the European Union - Hopkins, John (Victoria University of Wellington Law Review, 2007)
The development of the EU over the last 50 years is not the only revolution to have taken place in Europe. There has also been the emergence of sub-national entities and autonomous regional governments to represent them. These are accommodated in various constitutional arrangements throughout the EU. This paper argues that the development of supra-national governance must be recognised as a structure requiring a different approach from those of the executive dominated structures of international law. This paper examines in particular sub-national governments and their role in the EU and considers the capacity of supra-national structures to incorporate sub-national institutions and interests.